Tanggung Jawab Konsumen Terhadap Kerugian Pelaku Usaha Dalam Transaksi Pembuatan Baju di Garmen Dipa Production Kabupaten Badung - Ni Ketut Maya Ari Lestari; Ni Luh Made Mahendrawati; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2024)
A corporation is closely related to an agreement that gives rise to rights and obligations that bind all parties. During the implementation of cooperation with Dipa Production garments with consumers, there have been problems regarding the transaction process that is not carried out by consumers, causing losses to Dipa Production garments. The formulation of the problem is: How is the legal relationship between business actors and consumers in the transaction of making clothes in Dipa Production garment Badung Regency? And what are the legal consequences for consumers against the loss of business actors in shirt-making transactions at Dipa Production garment in Badung Regency? The research method used is empirical legal research. The approach to the problem used is a statutory and sociological approach. Dipa Production garment makes an agreement with consumers to make clothes. The occurrence of problems due to late consumer performance and non-performance. In this case, consumers have not completed their obligations, such as late payment transactions, and not making payment transactions. Settlement of default disputes for consumers who are late in paying, can be resolved by negotiating. Meanwhile, consumers who do not make payments cannot be contacted at all and disappear.